2007
DOI: 10.1111/j.1462-2920.2007.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural furanone (5Z)‐4‐bromo‐5‐(bromomethylene)‐3‐butyl‐2(5H)‐furanone disrupts quorum sensing‐regulated gene expression in Vibrio harveyi by decreasing the DNA‐binding activity of the transcriptional regulator protein luxR

Abstract: Summary This study aimed at getting a deeper insight in the molecular mechanism by which the natural furanone (5Z)‐4‐bromo‐5‐(bromomethylene)‐3‐butyl‐2(5H)‐furanone disrupts quorum sensing in Vibrio harveyi. Bioluminescence experiments with signal molecule receptor double mutants revealed that the furanone blocks all three channels of the V. harveyi quorum sensing system. In further experiments using mutants with mutations in the quorum sensing signal transduction pathway, the compound was found to block quoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 41 publications
5
152
0
5
Order By: Relevance
“…Bioluminescence in Vibrio harveyi is inhibited greater than 1,000-fold at micromolar concentrations of furanone (247). Correspondingly, survival of brine shrimp after challenges with pathogenic V. harveyi, Vibrio campbellii, and Vibrio parahaemolyticus improved with low-micromolar treatments of synthetic furanones (248).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 81%
“…Bioluminescence in Vibrio harveyi is inhibited greater than 1,000-fold at micromolar concentrations of furanone (247). Correspondingly, survival of brine shrimp after challenges with pathogenic V. harveyi, Vibrio campbellii, and Vibrio parahaemolyticus improved with low-micromolar treatments of synthetic furanones (248).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 81%
“…Intensive screening for small natural and synthetic compounds which inhibit QS resulted in the identification of several compounds which act by interfering with the binding of the AHL to the cognate Lux-family receptor, by decreasing its concentration via promotion of rapid protein turnover or also by decreasing its DNA binding activity (Defoirdt et al, 2007;Dong et al, 2007;Manefield et al, 2002). One of the most potent inhibitors found is an halogenated furanone produced by the seaweed Delisea pulchra and related synthetic derivatives Gonzalez and Keshavan, 2006;Hentzer et al, 2003a).…”
Section: Practical Applications In the Control Of Bacterial Ahl Quorumentioning
confidence: 99%
“…The natural compound (5Z)-4-bromo-5-(bromomethylene)-3-butyl-2(5H)-furanone from D. pulchra inhibits both acyl-homoserine lactone-based and autoinducer 2-based QS (Ren et al, 2001), and the synthetic furanone C-30 ( Figure 1a inset) has been shown to decrease acylhomoserine lactone-based signaling as well as decrease the virulence of P. aeruginosa in a mouse pulmonary infection model (Hentzer et al, 2003). These brominated furanones interrupt QS by interacting with transcriptional regulators that propagate the QS response (Defoirdt et al, 2007), and they do not affect bacterial growth in rich medium (Gram et al, 1996;Ren et al, 2001;Hentzer et al, 2003). However, growth of pathogens in the host during infections is more likely to involve non-robust carbon sources and may involve compounds whose utilization depends on QS (Defoirdt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%